2022
DOI: 10.1002/lary.30408
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of the Salivary Pepsin Test for the Diagnosis of Laryngopharyngeal Reflux

Abstract: Objective To investigate the optimal time point for diagnosing laryngopharyngeal reflux (LPR) through combining 24‐h hypopharyngeal‐esophageal multichannel intraluminal impedance‐pH (24‐h HEMII‐pH) monitoring and the multi‐time point salivary pepsin test (MTPSPT). Study Design Prospective uncontrolled trial. Method Patients with and without LPR symptoms were included as the test group and the control group, respectively. The patients in the test group underwent 24‐h HEMII‐pH and MTPSPT. The results of 24‐h HEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Currently, the common clinical sampling times of Peptest include fasting in the morning, 1 h after meals, and within 10 min after symptom. Zhang et al found that the diagnostic value of fasting and postprandial Peptest was the same 15 . However, Hayat et al found that the diagnostic accuracy of postprandial Peptest were significantly higher than fasting 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the common clinical sampling times of Peptest include fasting in the morning, 1 h after meals, and within 10 min after symptom. Zhang et al found that the diagnostic value of fasting and postprandial Peptest was the same 15 . However, Hayat et al found that the diagnostic accuracy of postprandial Peptest were significantly higher than fasting 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that the diagnostic value of fasting and postprandial Peptest was the same. 15 However, Hayat et al found that the diagnostic accuracy of postprandial Peptest were significantly higher than fasting. 12 The positive rate of post-symptom Peptest were higher than postprandial Peptest.…”
Section: F I G U R Ementioning
confidence: 98%
“…The 24‐hour multichannel hypopharyngeal‐esophageal multichannel intraluminal impedance‐pH monitoring (24 h HEMII‐pH) is considered to be the most accurate tool for diagnosing LPR, providing an objective picture of the occurrence of various types of LPR episodes. However, the 24 h HEMII‐pH is invasive, expensive, and not widely applied 3 . The clinical symptoms of LPR are not specific, but a composite LPR‐related symptom questionnaire can assist in screening of LPR.…”
Section: Introductionmentioning
confidence: 99%
“…However, the 24 h HEMII-pH is invasive, expensive, and not widely applied. 3 The clinical symptoms of LPR are not specific, but a composite LPR-related symptom questionnaire can assist in screening of LPR. As the easiest and quickest method, the symptom questionnaire is a screening tool that should not be overlooked in clinical practice.…”
Section: Introductionmentioning
confidence: 99%